Biostimulant enhances growth and corm production of saffron (Crocus sativus L.) in non-traditional areas of North western Himalayas - Chaudhary, Neha; Kothari, Deepak; Walia, Swati; Ghosh, Arup; Vaghela, Pradipkumar; Kumar, Rakesh (Frontiers in Plant Science, 2023)
The usage of seaweed extracts in cropping systems is gaining attention nowadays due to their distinct bioactive properties. This study aims to assess how saffron (Crocus sativus L.) corm production was affected by seaweed extract through different application modes. The study was conducted at the CSIR-Institute of Himalayan Bioresource Technology, Palampur, HP, India, during the autumn-winter agricultural cycle. Five treatments using a combination of Kappaphycus and Sargassum seaweed extracts were replicated five times in a randomized block design. Treatments that were examined include T1: Control, T2: Corm dipping @ 5% seaweed extract, T3: Foliar spray @ 5% seaweed extract, T4: Drenching @ 5% seaweed extract, and T5: Corm dipping + foliar spray @ 5% seaweed extract. Seaweed extract, when applied to saffron plants (T5: Corm dipping + foliar spray @ 5% seaweed extract) resulted in significantly higher growth parameters along with the higher dry weight of stem, leaves, corms, and total roots per corm. Corm production, viz., the number of daughter corms and corm weight per m2 was significantly affected by seaweed extract application, with the maximum value recorded with treatment T5. Biochemical parameters chlorophyll, carotenoids, and photosynthetic rate were higher in T5, while nutrient concentration was lowest in this treatment. Seaweed extracts improved corm production, making it a feasible alternative to limiting the application of conventional fertilizers, attenuating the effects on the environment, and enhancing corm number and weight.